Factor VIII Inhibitor Associated with Chlorpromazine-Induced Hepatic Injury - Glazier, Richard L; Crowell, Edward B, Jr. (Thrombosis and Haemostasis, 1977)
A 90-year-old man was given chlorpromazine for sedation and 2 weeks later developed cholestatic jaundice and subsequently a factor VIII inhibitor. His death 4 weeks after institution of chlorpromazine, from massive bleeding, coupled with the autopsy finding of intrahepatic cholestatic jaundice, suggests that both adverse reactions were due to the drug.